Dynamics of excretion of Eimeria spp oocysts in alpacas (Vicugna pacos) during peripartum - Enríquez Añamuro, Carlos (2024)
Infections of alpacas at very early ages suggest that the dams may act as asymptomatic carriers of some Eimeria species. The aim of this study was to determine the dynamics of Eimeria spp oocyst excretion in alpaca dams during the calving season at the "La Raya" Research and Production Centre, Puno, Peru. Faecal samples were taken from 50 clinically healthy alpacas of the Huacaya breed naturally infected with Eimeria spp in the two weeks prepartum, week of delivery and four weeks postpartum (period December 2018 - March 2019). Dams were categorized into three age groups [A: 3-4 (n=19), B: 5-8 (n=26) and C: 9-12 years (n=5)]. Sample analysis was carried out using Sheather solution flotation and McMaster techniques. The pregnant dams entered the calving season excreting E. punoensis [49/50 (98%)], E. alpacae [43/50 (86%)], E. lamae [5/50 (10%), and E. macusaniensis [3/50 (6%)] but not E. ivitaensis. The percentage of dams shedding oocysts of E. alpacae and E. punoensis increased after the second week postpartum, while it was found a minimal excretion load of E. macusaniensis and E. lamae before and after the calving season. There was a significant difference in opg between A and B, and between the two weeks prepartum and four weeks postpartum, in addition to a very low negative correlation (-0.0538) between the number of opg and age (p=0.0468). Animals infected with E. punoensis presented 6.5 times the prevalence of those parasitized with E. alpacae (p<0.001; 95% CI 2.33-18.13).